An Overview of Syzygium Polyanthum (Bay leaf) Extract as Dyslipidemia Treatment - Satya Agusmansyah (Open Access Indonesian Journal of Medical Reviews, 2021)
Dyslipidemia is one of the main risk factors for cardiovascular diseases, such as heart attack and stroke. This condition can be caused by genetic factors, unhealthy lifestyles (such as unhealthy food, lack of exercise, smoking, and excessive alcohol consumption), as well as some medical conditions, such as diabetes and hypothyroidism Syzygium polyanthum or also called Indonesian bay leaf is a tropical plant that usually grows in Southeast Asia. This literature review aimed to describe the benefits of bay leaves as adjuvant therapy in dyslipidemia. Apart from being used as a spice in cooking, Syzygium polyanthum is also known to have several health benefits. These leaves contain compounds such as eugenol, tannins, and flavonoids, which have antioxidant and anti-inflammatory effects. Several studies show that bay leaves can help lower blood sugar levels, improve heart health, and strengthen the immune system. In conclusion, bay leaf or Syzygium polyanthum has various kinds of compounds, such as flavonoids, eugenol, and tannins which are useful in lowering blood cholesterol. Its use as a therapy for dyslipidemia requires further study.